METODE PEMBELAJARAN PIANO TINGKAT DASAR DI GILANG RAMADHAN STUDIO BAND PADANG - Rocky Ferdinand Panjaitan; Olan Yogha Pratama (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to describe how the basic piano learning method is used at Gilang Ramadhan Studio Band (GRSB) Padang. It focuses on the learning method used only. This study uses a qualitative approach that produces descriptive data on the use of basic piano learning methods at Gilang Ramadhan Studio Band (GRSB) Padang. Data collection was carried out through observation, interviews, documentation, and data analysis consisting of data reduction, data presentation, and drawing conclusions. The results of the study showed that students were able to follow the learning well, were able to follow the instructor's instructions well so that students could play the piano gradually. In the learning process that took place using lecture, imitation, demonstration and practice methods. While the learning materials presented were introduction to musical notation, fingering, scale and sight reading. In addition, instructors always check at the beginning of the meeting and grade exams are not always used as a sign that students can move up to the next level. To get further benefits, based on the results of research and discussion on the use of basic learning methods at Gilang Ramadhan Studio Band (GRSB) Padang, it is necessary to have a combination of lecture methods with practice on the introduction to music notation material so that students can understand and apply theoretical concepts, speed adjustments in teaching materials especially when applying imitation and demonstration methods, variations in the use of drill methods to overcome boredom, mentoring and feedback so that students get clarification on the difficulties faced by students and the use of multimedia to make the material more interesting and easy to understand especially on the introduction to music notation material. Thus, the basic piano learning process at Gilang Ramadhan Studio Band (GRSB) Padang can be more effective and enjoyable.